PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN DAN KEBIJAKAN DIVIDEN TERHADAP MANAJEMEN LABA (Studi Pada Perusahaan Manufaktur Sektor Consumer Good Industry Yang Terdaftar Di Bursa Efek Indonesia) - Edon Ramdani; Aulya Ana Musdhalifah (LPPM Universitas Putera Batam, 2021)
Abstract The purpose of this research is to determine and provide empirical evidence regarding the effect of tax planning, deferred tax expense and dividend policy on earnings management in consumer goods industry companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The number of samples in this study were 12 companies obtained by using purposive sampling method based on predetermined criteria. The data used is secondary data in the form of an annual report for the period 2015 – 2019 taken from the www.idx.coid website. The data analysis technique used is descriptive statistical technique, panel data regression model, panel data regression model estimation, classical assumption test, coefficient of determination, f test (as a simultaneous test) and t test (as a partial test). The results of this study indicate that in a partial test, tax planning has no effect on earnings management, deferred tax expense affects earnings management and dividend policy has no effect on earnings management. While the results of the study simultaneously variable tax planning, deferred tax expense and dividend policy simultaneously affect earnings management. Keywords:Tax Planning, Defered Tax Expense, Dividen Policy, Earnings Management